Interventional pericardiology pericardiocentesis, pericardioscopy, pericardial biopsy, balloon pericardiotomy and intrapericardial therapy - Maisch, Bernhard; Pankuweit, Sabine; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Interventional Pericardiology gives a unique and comprehensive view on an often neglected but clinically very important part of cardiovascular disease: The pericardium and the adjacent myocardium or epicardium. The authors of this up-to-date compendium on pericardial disease etiology, diagnostics and treatment, Professors Bernhard Maisch (Marburg), Arsen Ristic (Belgrade), Petar Seferovic (Belgrade) and Teresa Tsang (Rochester) focus on recent advances to the new window that has been opened to the heart by flexible and video-assisted pericardioscopy, modern biochemical, immunohistological and molecular tools for the analysis of epicardial and pericardial biopsies, which have been acquired safely under pericardioscopic control by the interventional pericardiologist. Their book adds brand-new information to the recent and so far only guidelines world-wide by the European Society of Cardiology on the management of pericardial diseases. This task-force has been chaired by the lead author B. Maisch. Accordingly ?Interventional Pericardiology? belongs in every medical library and on the desk of every cardiologist, cardiological interventionalist, and trainee with an interest in pericardial diseases.
A Historical Perspective -- Anatomy of the Pericardium Relevant for Pericardial Access, Pericardioscopy, and Intrapericardial Interventions -- Pericardial Effusion and Cardiac Tamponade -- Pericardial Access and Drainage: Standard Techniques -- Alternative Techniques for Pericardiocentesis -- Pericardiocentesis in the Absence of Effusion -- Diagnostic Value of Pericardial Fluid Analyses -- Pericardiosopy: Endoscopic Insight in Pericardial and Epicardial Pathology -- Epicardial and Pericardial Biopsy -- Intrapericardial Treatment in Pericardial Disease -- Percutaneous Balloon Pericardiotomy -- Frontiers and Emerging Procedures.
Electronic reproduction.
Keywords: Pericardium -- Diseases -- Treatment; Pericardium -- Surgery; Electronic books